INNOVATION IN DIGITALIZATION OF HEALTH SERVICES: A LITERATURE REVIEW - Massora, Veriasari Rangga; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The review focuses on the process of putting in place health information systems that collect data and information, such as Android apps that make customer service easier. This innovation in digital information systems is one of the aspects that contribute to the usage of digital health systems, such as accessibility, peer influence, and, most crucially, trust. This study emphasizes the necessity for healthcare providers to establish efficient digital information systems, and healthcare providers, such as governments and non-profit organizations, should learn more about this issue. Innovations such as digital data capture will assist the Ministry of Health in storing data such as a person's weight, blood pressure, and the prevalence of a specific disease. The passage of time allows you to detect the progression of illness and receive treatment as soon as possible. This research aims to describe innovation in health services. This research uses a descriptive design with a literature review approach, articles are included in this review by journal databases: PubMed and Google Scholar. Based on the papers studied in the literature, it is possible to infer that health policymakers muste Based on the papers studied in the literature, it is possible to infer that health policymakers must be strong leaders. By embracing e-leadership and creating current and new digital solutions, health policymakers may boost the success rate of e-health creation and implementation, therefore benefiting physicians and patients. The use of digital technology in health services has the potential to dramatically enhance health care quality, efficiency, and accessibility. Keyword: Innovation, Information Systems, Health Services